Nanostructured hydroxyapatite networks: Synergy of physical and chemical cues to induce an osteogenic fate in an additive-free medium. (September 2018) - Sartuqui, J.; Gardin, C.; Ferroni, L.; Zavan, B.; Messina, P.V.
Graphical abstract: Abstract: Nanoscale topography plays a central role in adult-stem-cell-niches. In this study we have demonstrated that by an accurate material design, mimicking the composition and structure of bone extracellular matrix, it is possible to guide human adipose stem cells (hASCs) to attain an osteogenic commitment, in vitro, without the requirement of soluble additives or grow factors. Alkaline Phosphatase (ALP) activity and Alizarin Red S test demonstrated that hASCs cultured onto hydroxyapatite frameworks dry-coating differentiated into mature osteoblasts even in the absence of specific inducing factors. Optical and electron scanning microscopic (SEM) observations revealed a direct cellular-material interaction that indicated an appropriate communication between nanotopographical features and the integrin receptors in the cell´s focal adhesions. Real-time quantitative PCR (RT-qPCR) analysis confirmed the expression of specific markers of pre-osteoblast and mature osteoblast stages as osterix (OSX), osteopontin (OPN), osteocalcin (OC) and; specific markers of extracellular matrix maturation and mineralization stages as alkaline phosphatase (ALPL), collagen type I alpha 1 (COL1A1) and osteonectin (ON). Osteoprotegerin (OPG), ALPL, COL1A1, and sclerostin (SOST) expressions were up regulated compared to osteogenic differentiation media conditions.